2002
DOI: 10.1063/1.1522370
|View full text |Cite
|
Sign up to set email alerts
|

Effect of defects on the line shape of electron paramagnetic resonance signals from the single-molecule magnet Mn12: A theoretical study

Abstract: We herein estimate the effect of lattice defects on the line shape of electron paramagnetic resonance (EPR) signals from a single crystal of the S = 10 single-molecule magnet Mn 12 with the external magnetic field along the crystal c axis. A second-order perturbation treatment of an effective single-spin Hamiltonian indicates that a small, random, static misorientation of the magnetic symmetry axes in a crystalline lattice can lead to asymmetric EPR peaks. Full spectra are simulated by calculating probability-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…It has been suggested that the distribution in internal transverse fields could arise from a distribution in the magnetic easy axes of individual molecules. 16,17 But the origin of the distribution in the magnetic easy axes remains unknown. In this regard, we consider, within DFT, the possibility that extra electrons when accepted by Mn 12 molecules, will exhibit a disorder-or defect-induced behavior that is observed in the experimental samples.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the distribution in internal transverse fields could arise from a distribution in the magnetic easy axes of individual molecules. 16,17 But the origin of the distribution in the magnetic easy axes remains unknown. In this regard, we consider, within DFT, the possibility that extra electrons when accepted by Mn 12 molecules, will exhibit a disorder-or defect-induced behavior that is observed in the experimental samples.…”
Section: Introductionmentioning
confidence: 99%